JERUSALEM ARTICHOKE IS A PLANT OF 21ST CENTURY - M. A. Zhuchkova; S. G. Skripnikova (Овощи России)
In modern concept of healthy food the products of functional destination play a main role to neutralize the influences of unfavorable environments and unbalanced diet. The Jerusalem artichoke is a promising raw material to produce prebiotic and dietary food. Owing to increased content of biologically active substances (polyphenols, vitamins, pectin and mineral compounds) the Jerusalem artichoke is recognized as valuable product for human’s diet. Among other root-tuber vegetables the Jerusalem artichoke is distinguished by its high content of inulin that is regarded as an effective remedy to treat diabetes, atherosclerosis, obesity and different intoxications. On October 29, Ministry Council of Union State of Russia and Belarus accepted a program ‘Innovation and Improvement of Production in Potato and Jerusalem Artichoke’ aimed to develop high-yielding varieties and up-to-dated technology for production and post-harvesting processing, regarding to the biological features, namely the high contents of inulin, pectin, oligosaccharides in tubers and foliage. In Kaluga oblast, in the frame of program realization, an Innovative Agro-industrial Complex, ‘KiT’ is now under construction, where Jerusalem artichoke tubers and foliage are processed into inulin, fructose-oligosaccharides, fructose-glucose syrup, dietary and prebiotic puree, juice-contented drinks according to technology standards enable to preserve all valuable biologically active components. It allows manufacturing valuable biologically active products and ingredients, such as ‘live’ puree and juices.